Pengaruh Model Pembelajaran Problem Based Learning dan Media Poster Terhadap Hasil Belajar Siswa SMAN 2 Unggulan Tanah Grogot: Penelitian - Nurul Kholifah; Jailani; Sri Purwati (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This research investigates the impact of applying a problem-based learning (PBL) model supported by poster media on the learning outcomes of eleventh-grade students at SMAN 2 Unggulan Tanah Grogot. The integration of posters within the PBL approach is intended to enhance student engagement in biology lessons by presenting authentic problems that encourage critical and creative thinking. A quasi-experimental method was employed involving two groups: an experimental group taught using the poster-assisted PBL model and a control group taught through conventional lecture-based instruction. Data collection was conducted using pretest and posttest instruments consisting of validated multiple-choice and essay questions. The findings revealed a notable improvement in the experimental group’s average posttest score, rising from 66 to 80, while the control group showed an increase from 65 to 75. Statistical analysis indicated that the poster-assisted PBL model had a significant influence on students’ learning outcomes at a significance level of p < 0.05. Furthermore, this learning model not only improved overall achievement but also minimized differences in comprehension among students in the experimental group. The use of poster media as a visual aid proved effective in facilitating students’ understanding of complex biological topics, including human anatomy and the circulatory system. In conclusion, the implementation of innovative instructional models such as poster-assisted PBL enhances students’ conceptual understanding while fostering a more interactive and enjoyable learning environment. Therefore, this approach is recommended for adoption in other educational settings.